2015 International Conference on Signal Processing and Communication Engineering Systems 2015
DOI: 10.1109/spaces.2015.7058213
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microstrip rectangular carpet shaped fractal antenna

Abstract: The need for miniaturized antenna is ever growing in view of the advancements in wireless communication technology.The conventional microstrip antennas take any shape like square, rectangular, triangle and so on. They provide normally single resonance frequency with high quality factor because of narrow bandwidth. However, the fractal antennas are able to provide either multi-band resonances or broad bandwidth because of the self-similar and space-filling properties.In present paper, a study is made on Sierpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Comparisons of different existing antennas such as tri-band [1], Koch [2], microstrip fractal [3] and rectangular carpet [5] have been made with the proposed antenna (Giuseppe peano) in this paper. By observing the results of existing antennas and proposed antenna, it has been concluded that the maximum gain of existing antennas is 6.8dB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparisons of different existing antennas such as tri-band [1], Koch [2], microstrip fractal [3] and rectangular carpet [5] have been made with the proposed antenna (Giuseppe peano) in this paper. By observing the results of existing antennas and proposed antenna, it has been concluded that the maximum gain of existing antennas is 6.8dB.…”
Section: Discussionmentioning
confidence: 99%
“…Koch fractal [2] antenna shows the value of gain as 6.8dB, 4.9dB and 2.8dB at respective frequency band. Similarly, the microstrip fractal [3] and rectangular carpet [5] shows the overall gain of 4dB and 3.8dB respectively. To increase the gain and the resonant frequencies the proposed antenna is designed.…”
Section: Gainmentioning
confidence: 96%
See 2 more Smart Citations
“…Two properties are used to design the geometries of fractal antennas, one is selfsimilarity and the other is space-filling [5] [6]. Self-similarity property of fractal is used to divide the parts of whole structure at different scales and space-filling is used to achieve the miniaturization of antenna [7]. The geometries of fractal antenna are designed to achieve the wideband and multiband characteristics which are the need of modern wireless communication systems [8].…”
Section: Introductionmentioning
confidence: 99%